2018
DOI: 10.7717/peerj.4746
|View full text |Cite
|
Sign up to set email alerts
|

Exotic lagomorph may influence eagle abundances and breeding spatial aggregations: a field study and meta-analysis on the nearest neighbor distance

Abstract: The introduction of alien species could be changing food source composition, ultimately restructuring demography and spatial distribution of native communities. In Argentine Patagonia, the exotic European hare has one of the highest numbers recorded worldwide and is now a widely consumed prey for many predators. We examine the potential relationship between abundance of this relatively new prey and the abundance and breeding spacing of one of its main consumers, the Black-chested Buzzard-Eagle (Geranoaetus mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…For instance, current Lepus europaeus densities in northern Patagonia, reaching up to 250 individuals per km 2 (Barbar et al. ), reduce the carrying capacity of agricultural land by one sheep every two hectares (Bonino , ). Other estimates are even worse, suggesting that, at this density, Lepus europaeus may consume nearly 15% of the palatable plants available for livestock in meadows (Amaya ).…”
Section: Economic Consequences Of Introductionsmentioning
confidence: 99%
“…For instance, current Lepus europaeus densities in northern Patagonia, reaching up to 250 individuals per km 2 (Barbar et al. ), reduce the carrying capacity of agricultural land by one sheep every two hectares (Bonino , ). Other estimates are even worse, suggesting that, at this density, Lepus europaeus may consume nearly 15% of the palatable plants available for livestock in meadows (Amaya ).…”
Section: Economic Consequences Of Introductionsmentioning
confidence: 99%
“…Hare populations are currently widespread, but at relatively low densities (Pasqualotto et al. in press ) compared to other regions of Brazil and South America (Barbar et al., 2018; Kasper et al., 2012; Novaro et al., 2000). Even if the species' realized niches overlap substantially, low hare densities would naturally lead to a weak competitive interaction with the Brazilian cottontails, as supported by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…An important caveat to this finding is that we investigated current patterns of nest‐site selection for a relatively short study period. The patterns of selection we observed were after the construction of energy infrastructure so we lacked the ability to understand potential changes before and after development of long‐term demographic responses of raptor or prey populations that could ultimately affect nearest‐neighbor distance and raptor nest density (Skalski et al 2005, Barbar et al 2018). However, we also demonstrated that more‐selected habitat (90% of use based on independent historical nests) for ferruginous hawks and golden eagles intersected the areas of greatest potential and current development of oil/gas reserves and wind energy.…”
Section: Discussionmentioning
confidence: 99%